Repetitive somatic embryogenesis and plant regeneration in Garcinia indica Choiss - Thengane, Shubhada Ratnakar; Deodhar, Swapna R.; Bhosle, S. V.; Rawal, S. K. (In Vitro Cellular & Developmental Biology-Plant, 2006)
Immature seeds of Garcinia indica Choiss. were excised from immature fruits and cultured on Lloyd and McCown (1980), woody plant medium (WPM) with different combinations of auxins and cytokinins. Somatic embryos were obtained on the media supplemented with 6-benzylaminopurine (BA; 2.2-22.1 mu M) alone or in combination with alpha-naphthalene acetic acid (NAA; 2.6 mu M) with 80% frequency within a period of 2-3 wk. Subculture of embryos on medium containing BA (16.0 mu M) supplemented with indole-3-acetic acid (IAA; 2.8-5.7 mu M) and/or kinetin (4.6 mu M) gave rise to clusters of secondary somatic embryos along with maturation of primary embryos. In subsequent subculture on hormone-free half-strength WPM, the embryo clusters germinated with an increase in the number of secondary somatic embryos. About 70% of somatic embryos germinated into complete plantlets, which were successfully established under greenhouse conditions.
Keywords: Garcinia indica; guttifereae; secondary somatic embryos; seeds; somatic embryos